Implementasi Strategi Pemasaran dalam Upaya Meningkatkan Volume Penjualan Toko Kelontong Kecamatan Benowo Surabaya - Elvini Nashafira; Acep Samsudin (International Forum of Researchers and Lecturers, 2024)
Grocery stores are a very important type of business in society, especially in urban areas. However, in increasingly fierce competition, grocery stores must always innovate in developing marketing strategies to increase purchasing power, retain old customers and attract new customers. This research aims to provide an understanding of effective marketing strategies both offline and online. The results of this research show that grocery stores in Benowo District, Surabaya implement diverse and targeted marketing strategies to increase the sales volume of their products in market share.